The effect firm characteristic on corporate social responsibility disclosure in the firms listed in Indonesia Sharia Stock Index - Ahmad Rifani Irham; Sa'adah Yuliana; Marlina Widiyanti (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
This study aims to analyze the effect of firm characteristics of corporate social responsibility disclosure. The population in this study is as many as 143 companies listed in the Indonesia Sharia Stock Index, whereas units of analysis in this study were 43 companies listed in the Indonesia Sharia Stock Index for the period 2012-2016. The type of data used is secondary data with multiple linear regression analysis. The result shows that firm size and profitability have significant influence, while leverage and firm growth have no significant effect on corporate social responsibility disclosure. This study supports signaling theory in which the information presented will be a good signal for external parties for sustainable development for the company.